Certain class of m-fold functions by applying Faber polynomial expansions - MOTAMEDNEZHAD, Ahmad; SALEHIAN, Safa (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
In this paper, we introduce new class Σm(µ, λ, γ, β) of m-fold symmet- ric bi-univalent functions. Furthermore, we use the Faber polynomial expansions to find upper bounds for the general coefficients |amk+1|(k >= 2) of functions in the class Σm(µ, λ, γ, β). Moreover, we obtain estimates for the initial coefficients |am+1| and |a2m+1| for functions in this class. The results presented in this paper would generalize and improve some recent works. Mathematics Subject Classification (2010): 30C45, 30C80.